2014
DOI: 10.5830/cvja-2014-040
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after hospital discharge in patients admitted with heart failure in Abeokuta, Nigeria : data from the Abeokuta Heart Failure Registry : cardiovascular topic

Abstract: SummaryBackgroundCompared to other regions of the world, there is a paucity of data on the short-term outcome of acute heart failure (AHF) in Africa’s most populous country, Nigeria. We examined the six-month outcomes (including case fatalities) in 285 of 309 AHF subjects admitted with HF to a tertiary hospital in Abeokuta, Nigeria.MethodsThe study cohort of 285 subjects comprised 150 men (52.6%) and 135 women (47.4%) with a mean age of 56.3 ± 15.6 years and the majority in NYHA class III (75%).ResultsThere we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…In addition, our results reaffirm other predictors of mortality following hospitalization with heart failure including increasing alcoholic drinks per sitting, New York Heart Association (NYHA) functional class IV heart failure [32, 33]. This is likely explained by the late presentation with advanced disease [12, 34].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, our results reaffirm other predictors of mortality following hospitalization with heart failure including increasing alcoholic drinks per sitting, New York Heart Association (NYHA) functional class IV heart failure [32, 33]. This is likely explained by the late presentation with advanced disease [12, 34].…”
Section: Discussionsupporting
confidence: 83%
“…However, there are no similar studies from sub-Sahara Africa for comparison of these results. In addition, we found that the cumulative incidence death among participants with New York heart association (NYHA) functional class IV at time of hospitalization was higher than that of participants with NYHA class III as has been shown by others [13,25]. This could be explained by the late presentation with advanced heart failure class given the long distances travelled to reach health facilities as well as time delays in lower level centers where diagnostic and therapeutic expertise is limited [26,27].…”
Section: Discussionsupporting
confidence: 71%
“…Also, compared to other prior studies from sub-Saharan Africa, we found a higher incidence of in-hospital mortality. This maybe attributable to the fact that prior studies were carried out in highly specialized cardiac centers with superior diagnostic, therapeutic, and human resources thus the lower in-hospital mortality rate while the current study was performed in general medicine ward of a regional hospital which is generalizable to the level of care where majority of heart failure patients seek care in low income countries such as Uganda [13,21]. Taken together, this finding expounds on the existing literature on all-cause mortality among heart failure patients in sub-Saharan Africa that, until now, reported only deaths occurring in hospitals, as such reported lower incidence of death associated with acute heart failure [12,13,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm the findings of Ogah et al in Nigeria [ 50 ], who reported that more than two thirds of patients were lost to follow-up. Several reasons can explain why some patients leave the hospital, e.g.…”
Section: Discussionsupporting
confidence: 91%